2002
DOI: 10.1017/s0950268801006574
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of conventional influenza vaccination in asthmatic children

Abstract: SUMMARYInfluenza immunization rates among young asthmatics remain unsatisfactory due to persistent concern about the impact of influenza and the benefits of the vaccine. We assessed the effectiveness of the conventional inactivated trivalent sub-unit influenza vaccine in reducing acute respiratory disease in asthmatic children. We conducted a two-season retrospective cohort study covering the 1995-6 and 1996-7 influenza outbreaks in 22 computerized primary care practices in the Netherlands. In total, 349 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 40 publications
2
19
0
3
Order By: Relevance
“…32 The number of febrile influenza A episodes was reduced by 68% 33 in a study among children, and acute respiratory disease was reduced by 55% among children with asthma in a previous small cohort study by our group. 34 In the present study, we observed a 43% reduction in GP visits for acute respiratory disease and acute otitis media during the 1999-2000 influenza epidemic, an estimate that is in accordance with most of these earlier small-scale studies. However, we lacked adequate power to establish a potential association between vaccination status and the more severe end points (ie, hospitalization or death) among these children.…”
Section: Commentsupporting
confidence: 93%
“…32 The number of febrile influenza A episodes was reduced by 68% 33 in a study among children, and acute respiratory disease was reduced by 55% among children with asthma in a previous small cohort study by our group. 34 In the present study, we observed a 43% reduction in GP visits for acute respiratory disease and acute otitis media during the 1999-2000 influenza epidemic, an estimate that is in accordance with most of these earlier small-scale studies. However, we lacked adequate power to establish a potential association between vaccination status and the more severe end points (ie, hospitalization or death) among these children.…”
Section: Commentsupporting
confidence: 93%
“…Such studies should focus on age and underlying asthma in particular. There are limited data to support the efficacy of influenza vaccination in reducing asthma exacerbations, 17 particularly in older children, 18 although previous concerns about safety in asthma have been assuaged. Asthma has therefore been an indication for influenza vaccination for several years, but uptake is low.…”
Section: Discussionmentioning
confidence: 99%
“…In a nonrandomized controlled trial during the 1992-93 season involving 137 children who had moderate to severe asthma, vaccine efficacy against laboratory-confirmed influenza A(H3N2) infection was 54% among children aged 2 through 6 years and 78% among children aged ≥7 through 14 years; vaccine efficacy against laboratory-confirmed influenza B infection was 60% among children aged ≥7 through 14 years, but nonsignificant for the younger age group (193). In a two-season study of 349 asthmatic children, IIV3 vaccine was associated with a 55% reduction in the occurrence of ARI in children aged <6 years (95% CI = 20-75; p = 0.01), but no association was noted among children aged 6 through 12 years (194).…”
Section: Persons With Chronic Medical Conditionsmentioning
confidence: 92%